Performance of Butanol Separation from Abe Mixtures by Pervaporation Using Silicone-Coated Ionic Liquid Gel Membranes - Romero-Figueroa, J; Quijada-Maldonado, E; Merlet-Venturelli, G; Cabezas-Cornejo, R; Torres-Mediano, A (Royal Society of Chemistry, 2019)
This work aims at the separation of n-butanol from aqueous solutions by means of pervaporation using membranes based on gelled ionic liquids (IL). These membranes were mechanically stabilized with a double silicone coating using two polydimethylsiloxane (PDMS) films. The first step of the membrane preparation considered the formation of a gelled ionic liquid layer, which was formed using two different imidazolium-based ionic liquids: [omim][Tf2N] and [bmim][Tf2N], and two different phosphonium-based ionic liquids: [P6,6,6,14][Tf2N] and [P6,6,6,14][DCA]. The gelation procedure was carried out on a porous paper support using a low molecular weight gelator. The membranes obtained from this method were tested in pervaporation assays to separate butanol from model ABE (Acetone-Butanol-Ethanol) fermentation solutions. These assays were done in an experimental setup especially built for this purpose. The pervaporation performance of these ionic liquid-based membranes was compared to that obtained with a single PDMS layer membrane. From these experimental results, butanol/water selectivity for [P6,6,6,14][Tf2N]-based membranes reached a value equal to 892, which is 150 times higher than the value obtained for a single PDMS layer membrane. Simultaneously, for the same IL, the transmembrane fluxes (kg h-1 m-2) of butanol and water were 37% and 99.6% lower than the values obtained using a single PDMS layer membrane, respectively. The hydrophobic character of the selected ionic liquid and its relatively high values for the transport parameters can explain this experimental response. © 2019 The Royal Society of Chemistry.